Accuracy and prognostic role of NCCT-ASPECTS depend on time from acute stroke symptom-onset for both human and machine-learning based evaluation - Potreck, Arne; Weyland, Charlotte S.; Seker, Fatih; Neuberger, Ulf; Herweh, Christian; Hoffmann, Angelika; Nagel, Simon; Bendszus, Martin; Mutke, Matthias Anthony (Clinical neuroradiology, 2022)
We hypothesize that the detectability of early ischemic changes on non-contrast computed tomography (NCCT) is limited in hyperacute stroke for both human and machine-learning based evaluation. In short onset-time-to-imaging (OTI), the CT angiography collateral status may identify fast stroke progressors better than early ischemic changes quantified by ASPECTS.
Gesehen am 12.09.2023
Online veröffentlicht: 28. Oktober 2021